2015
DOI: 10.1186/s40064-015-0899-5
|View full text |Cite
|
Sign up to set email alerts
|

Levels of essential and non-essential metals in ginger (Zingiber officinale) cultivated in Ethiopia

Abstract: BackgroundGinger (Zingiber officinale Roscoe) is a common condiment for various foods and beverages and widely used worldwide as a spice. Its extracts are used extensively in the food, beverage, and confectionary industries in the production of products such as marmalade, pickles, chutney, ginger beer, ginger wine, liquors, biscuits, and other bakery products. In Ethiopia, it is among the important spices used in every kitchen to flavor stew, tea, bread and local alcoholic drinks. It is also chiefly used medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
47
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 31 publications
10
47
6
Order By: Relevance
“…This was reflected in the relatively high standard deviations and the remarkable differences between the mean and the median of the elemental contents (Tables 5-6). Similar results were reported by other studies for different spices [17,19,23,[25][26]. This variability is usually explained in terms of the effects of various ecosystems on the elemental levels at different regions.…”
Section: Variability Of Elemental Concentrations In Different Spicessupporting
confidence: 80%
“…This was reflected in the relatively high standard deviations and the remarkable differences between the mean and the median of the elemental contents (Tables 5-6). Similar results were reported by other studies for different spices [17,19,23,[25][26]. This variability is usually explained in terms of the effects of various ecosystems on the elemental levels at different regions.…”
Section: Variability Of Elemental Concentrations In Different Spicessupporting
confidence: 80%
“…This could be one reason behind the high value of Fe in Ethiopian maize. [26,27]. The determination of levels of toxic metals was also carried out in this study and Cd was found to be below detection limit of the instrument.…”
Section: Comparison Of Metal Levels Of the Present Study With Literatmentioning
confidence: 81%
“…The optimum condition is the one which require minimum reagent volume consumption, minimum reflux time, clarity of digests, and ease of simplicity [21][22][23][24][25][26]. In this study, to prepare a clear sample solution suitable for the analysis using AAS, a lot of trials of digestion procedures were made on the maize seed powder using the HNO 3 , H 2 O 2 and HClO 4 acid mixtures by varying parameters such as volume of the acid mixture, digestion time and digestion temperature to optimize the digestion procedure (Tables 1 and 2).…”
Section: Digestion Of the Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently some studies have been carried out on the mineral composition of selected spices (thyme, fennel, ginger, korarima, and red pepper) cultivated in Ethiopia (DERBIE;CHANDRAVANSHI, 2011;ENDALAMAW;WAGESHO;MEKASSA;TEFERA;CHANDRAVANSHI, 2016). Several global studies were also been done on Trigonella foenum-graecum (fenugreek) especially in the areas of medicine and to determine the metal content.…”
Section: Introductionmentioning
confidence: 99%